Presidency of Germany at OSCE in 2016 in the context of Russian-German relations - Angelina Bezrukova (Контуры глобальных трансформаций: политика, экономика, право, 2016)
In 2016 Germany will become the OSCE chairman. As the OSCE chairman Germany plans to pay special attention on such issues as the OSCE modernization, the Ukraine conflict solving and conventional arms control. Perhaps the responsibility imposed on Germany in the framework of the OSCE may lead to a revision of the general principles of German foreign policy, particularly with regard to Russia.